EVALUATION OF ANTICANCER POTENTIAL OF ETHANOLIC EXTRACT OF ALANGIUM SALVIFOLIUM LEAVES IN ANIMAL MODELS - C, PRATHIMA; SHASHIKUMARA, SHASHIKUMARA; T, THIPPESWAMY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aims to evaluate the anticancer potential of ethanolic extract of Alangium salvifolium leaves (EASL) against Ehrlich ascites carcinoma (EAC) in animal model. Methods: The ethanolic extract of A. salvifolium was prepared by continuous method using Soxhlet apparatus. Phytochemical analysis of EASL was conducted. Anticancer activity of the extract was evaluated by EAC model in Swiss albino mice. EASL was administered at the doses of 100 and 200 mg/kg body weight once a day orally for 14 days, after 24 h of tumor inoculation. Results: A. salvifolium leaves extract treatment produced significant decrease in tumor volume and body weight, and increase in total and non-viable cell count, along with elevated life span of EAC-bearing mice. The EASL exhibited potent dose-dependent antitumor activity. Further, the altered hematological parameters such as red blood cells, hemoglobin, and white blood cells levels as well as biochemical parameters such as serum glutamic oxaloacetic transaminase, serum glutamate pyruvate transaminase, alkaline phosphatase, albumin, and total protein levels in EAC mice were significantly (p<0.05) regained following treatment with EASL. The anticancer potential of EASL can be attributed to the presence of phenols and flavonoids. Conclusion: Results suggest that EASL possesses significant anticancer activity against EAC tumor-bearing Swiss albino mice.